Foundations of evidence-based social work practice - Roberts, Albert R.; Yeager, Kenneth. (Oxford University Press, 2006)
"Concise introduction to evidence-based social work that introduces the issues and methods most frequently encountered while preparing for evidence-based social work practice"--Provided by publisher.